Tantangan Nigeria Dalam Mencapai Poin 6 SDGs (Air Bersih dan Sanitasi Layak): Studi Kasus Pencemaran Lingkungan Delta Niger oleh Shell Company - Tri Utami, Arum; Ardyanti, Moza (UIN ALAUDDIN MAKASSAR, 2025)
Environmental pollution is one of the key issues that is a major concern in the Sustainable Development Goals (SDGs). One country that remains actively engaged in achieving the SDGs is Nigeria, which continues to face environmental pollution challenges, particularly in the Niger Delta region, where environmental degradation has resulted from oil mining activities by Shell Company. The impact of these mining activities has significantly affected water cleanliness in the Niger Delta, which aligns with SDG Goal 6, focusing on water sanitation. This case study highlights the environmental pollution caused by Shell's oil extraction activities in the Niger Delta and how this has become a major obstacle in achieving SDG Goal 6: